2017
DOI: 10.1115/1.4037652
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Efficiency-Power Tradeoff for an Air Compressor/Expander

Abstract: An efficient and power dense high pressure air compressor/expander (C/E) is critical for the success of a compressed air energy storage (CAES) system. There is a tradeoff between efficiency and power density that is mediated by heat transfer within the compression/expansion chamber. This paper considers the optimal control for the compression and expansion processes that provides the optimal tradeoff between efficiency and power. Analytical Pareto optimal solutions are developed for the cases in which hA, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is a common problem with hydropneumatic devices when adapted for energy system applications. The trade-off effects grow worse when the pressure source is variable, as described in [85]. Instead of improving the efficiency, the authors of [86] developed maximum power point tracking (MPPT) for hydraulic pumps and motors for accumulator based CAES systems.…”
Section: Optimization Strategies For Hydropneumatic Energy Convertersmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a common problem with hydropneumatic devices when adapted for energy system applications. The trade-off effects grow worse when the pressure source is variable, as described in [85]. Instead of improving the efficiency, the authors of [86] developed maximum power point tracking (MPPT) for hydraulic pumps and motors for accumulator based CAES systems.…”
Section: Optimization Strategies For Hydropneumatic Energy Convertersmentioning
confidence: 99%
“…Compression/expansion pressure profile control is a strategy that can ensure that both the power density and energy converter efficiency metrics fall within the optimal Pareto front. The authors of [85] developed a compression trajectory that uses a generalized heat transfer coefficient h and the surface area A as constants. In reality, the LP's heat transfer does not operate with such a constant hA parameter.…”
Section: Optimal Trajectorymentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results indicated that when the plate inserts with a height of 0.2 m, 0.35 m, and 0.5 m, the compression efficiency could be increased by approximately 3%, 4%, and 8%, respectively. Rice et al [25] proposed an optimal trajectory control method to solve the trade-off between power density and efficiency. The results showed that the proposed solutions could improve the power density and keep efficiency unchanged.…”
Section: Introductionmentioning
confidence: 99%